Efforts To Improve Cultural Literacy Through Learning Regional Dance - Aprilita Ni’matul Madinah; Elly Purwanti; Sefriyanti Sefriyanti (Aulad: Journal on Early Childhood, 2026)
Cultural literacy is essential in early childhood as it shapes character, national identity, and appreciation of local culture from a young age. This study aims to improve children’s cultural literacy through learning regional dance, specifically Lampung Dance, at ECE Budi Luhur II. The study uses a descriptive qualitative method involving teachers, 5–6-year-old students, and the principal, with instruments including observation, interviews, and documentation. Data were analyzed through descriptive analysis by comparing children’s development outcomes across learning cycles. The results show a significant improvement, with children achieving the Very Good Development (BSB) category increasing from 26.67% in Cycle 1 to 73.33% in Cycle 2. These findings imply that regional dance learning is an effective, interactive, and enjoyable strategy to enhance cultural literacy and foster children’s cultural identity.